The combined effect of bed-to-nurse ratio and nurse turnover rate on in-hospital mortality based on South Korean administrative data: a cross-sectional study - Hyun-Young Kim; Yunmi Kim; Jiyun Kim (BMC Nursing)
Abstract Background and aim Nurse staffing levels are associated with patient mortality, but little is known regarding the association between nurse turnover rate and patient mortality. This study investigated the combined effect of the bed-to-nurse ratio and the nurse turnover rate on in-hospital mortality in patients admitted to Korean acute care hospitals using national administrative data. Methods This study analyzed data from the National Health Insurance Service (NHIS) on 459,113 admitted patients and 111,342 employed nurses in 403 hospitals in South Korea from January to December 2016. Differences in in-hospital mortality and nurse turnover among hospital characteristics, including the bed-to-nurse ratio, were explored using the chi-square test. Multilevel, multivariate GEE logistic regression analyses were used to examine the combined effect of the bed-to-nurse ratio and the nurse turnover rate on in-hospital mortality. Results During the study period, 13,675 (3.0%) patients died during hospitalization, and 13,349 (12.0%) nurses left their jobs. The risk of death among patients admitted to hospitals with a bed-to-nurse ratio of < 2.5 and a nurse turnover rate of ≥ 12% was lower than among patients admitted to hospitals with a bed-to-nurse ratio of ≥ 4.5 and a nurse turnover rate of ≥ 12% (odds ratio [OR] = 0.63; 95% confidence interval [CI], 0.48–0.82). The risk of in-hospital mortality decreased further when the nurse turnover rate was < 12% (OR = 0.59; 95% CI, 0.44–0.79). Conclusion The bed-to-nurse ratio and nurse turnover rate were jointly associated with patient mortality. When hospitals with a low bed-to-nurse ratio also experienced high nurse turnover, the risk of in-hospital mortality was even greater. The finding of this study will help health policy makers to better understand the importance of both nursing staffing levels and nurse turnover rates. It is necessary to create a comprehensive improvement plan that integrates policies aiming to improve nurse staffing levels and reduce turnover rates into a single strategy.